Bimetal monatomic catalyst containing oxygen vacancy as well as preparation method and application of bimetal monatomic catalyst
By using bimetallic single-atom catalysts containing oxygen vacancies, the problem that the prior art cannot effectively degrade sludge extracellular polymers is solved, deep cracking of sludge and efficient release of organic matters is achieved, and the resource utilization of sludge is promoted.
Patent Information
- Application Number
- CN202411477417.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-25
Smart Images

Figure CN119500179A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrothermal oxidation sludge treatment catalysts, and in particular to a bimetallic single-atom catalyst containing oxygen vacancies, and a preparation method and application thereof. Background Art
[0002] The activated sludge method is mainly used in the biological treatment of urban sewage. The mechanism of activated sludge treatment of sewage is as follows: in the sewage treatment process, the bacterial flocs oxidize and decompose various organic substances in the wastewater into carbon dioxide and water, and at the same time generate flocs, at which time the microbial group of activated sludge is formed. The activated sludge absorbs some pollutants in the sewage and flocculates and settles, producing a large amount of residual sludge.
[0003] Sludge is mainly composed of sludge flocs and water. Sludge flocs are mainly composed of two parts: cell bodies and extracellular polymers. Extracellular polymers are mainly composed of proteins and polysaccharides. Polysaccharide molecules are rich in hydrophilic functional groups such as hydroxyl and carboxyl groups. They can form a stable and elastic network structure through adsorption and bridging, and cross-linking and fixing free cells is beneficial to sludge flocculation. Proteins and lipids can maintain the stability of the floc structure and improve the biological flocculation of sludge accordingly. Polysaccharide molecules, proteins and lipids form a compact and dense network structure through electrostatic forces, hydrogen bonding, ion attraction, biochemistry and other effects, which can serve as a protective layer for microorganisms to resist the invasion of adverse factors such as external heavy metals and toxic compounds. Therefore, the presence of extracellular polymers is also the main reason for the difficulty in sludge degradation. At the same time, the various forces inside / between extracellular polymers make the water in the sludge tightly bound inside / between the sludge flocs through adsorption or chemical bonds, which ultimately leads to a high moisture content in the sludge and is not easy to dehydrate.
[0004] The problem of excess sludge generated during sewage treatment is becoming increasingly serious. Traditional sludge treatment technologies include anaerobic digestion, dehydration, landfill, incineration, etc. However, traditional sludge treatment technologies have fatal problems such as high cost and secondary pollution, and cannot realize the resource utilization of sludge.
[0005] Hydrothermal Oxidation (HTO) is widely used in the field of organic wastewater and solid waste treatment due to its green and efficient advantages. The reaction with an oxidant in an aqueous solution under high temperature and high pressure conditions in a closed system is a hydrothermal oxidation reaction. Hydrothermal oxidation conditions can effectively release the water component in the sludge, and at the same time break the cell structure in the sludge, thereby releasing the organic matter in it and dissolving it in the liquid phase, thereby achieving sludge stabilization, harmlessness and reduction. In addition, the released organic matter is dissolved in the supernatant, and a large amount of soluble organic matter is oxidized and degraded into volatile fatty acids VFAs and other organic matter such as carbohydrates and proteins under oxygen-rich conditions, which can be used as substrates for the metabolism of various microorganisms. It is a high-quality carbon source and realizes resource utilization. However, the existing HTO technology cannot effectively degrade the extracellular polymers of the sludge, resulting in a low degree of degradation of the extracellular polymers of the sludge, and thus cannot achieve deep decomposition of the sludge, resulting in a high content of organic matter in the treated sludge and incomplete carbon source recovery. Summary of the invention
[0006] The present invention provides a bimetallic single-atom catalyst containing oxygen vacancies and a preparation method and application thereof to overcome the above problems.
[0007] On the one hand, the present invention provides a bimetallic single-atom catalyst containing oxygen vacancies, comprising a carrier and two active metal components loaded on the carrier in the form of single atomic centers, wherein the carrier is a composite metal oxide containing oxygen vacancies, and the two active metal components include a first metal and a second metal, wherein the total loading amount of the first metal is a, 0.2wt%≤a≤5.0wt%, and the total loading amount of the second metal is b, 0.2wt%≤b≤5.0wt%.
[0008] Furthermore, the first metal is selected from one of Fe, Mn and Cu, and the second metal is selected from one of Ru and Pd;
[0009] The composite metal oxide containing oxygen vacancies is selected from TiO 2 、ZrO 2 and Al 2 O 3 Any two metal oxides in the range of 2:8 to 8:2 are selected from the group consisting of:
[0010] Another aspect of the present invention provides a method for preparing a bimetallic single-atom catalyst containing oxygen vacancies, comprising the following steps:
[0011] S1: Preparation of composite oxide supports containing oxygen vacancies by hydrothermal method:
[0012] Dispersing 10 g of the mixture of the composite metal oxides containing oxygen vacancies into 200 mL of ethanol to obtain a mixed solution, placing the mixed solution in a reactor for heating reaction after ultrasonic mixing, and after the reaction is completed, cooling, centrifuging, washing, and drying to prepare a composite oxide carrier containing oxygen vacancies;
[0013] S2: The active metal is dispersed on the carrier in the form of single atoms by impregnation method:
[0014] The nitrate containing the first metal and the nitrate containing the second metal are dissolved in an aqueous solution containing 10 wt.% nitric acid to obtain an aqueous solution containing active metal salts, and the composite oxide support containing oxygen vacancies prepared in S1 is impregnated in the aqueous solution containing active metal salts, and ultrasonically impregnated for 0.5 to 1.0 h, and then dried at 60°C to constant weight, and the dried product is calcined in an inactive atmosphere for 2 to 4 h at a calcination temperature of 400 to 600°C. The calcined product is rinsed and dried to prepare a single-atom catalyst containing oxygen vacancies.
[0015] Furthermore, in S2, the mass ratio of the composite oxide support containing oxygen vacancies, the first metal nitrate, and the second metal nitrate is 1-10: 0.02-0.05: 0.02-0.05; the volume ratio of the mass of the composite oxide support containing oxygen vacancies to the aqueous solution containing active metal salts is (0.2-3.6) g: (20-100) mL.
[0016] Furthermore, in S1, the mixed solution is placed in a reaction kettle and heated for 6 to 24 hours at a temperature of 150 to 250°C;
[0017] The ultrasonic time is 30 minutes, and the ultrasonic frequency is 40 Hz;
[0018] The centrifugation, washing and drying steps are as follows: centrifugation at 5000 r / min for 120 s, washing the obtained solid product with deionized water and alcohol three times respectively, and drying in an oven at 80° C. to constant weight.
[0019] Furthermore, in S2, the specific steps of rinsing and drying are as follows: the product obtained after calcination is rinsed three times with deionized water and 10 wt.% nitric acid respectively, and then placed in a 60° C. vacuum oven and dried to constant weight.
[0020] Furthermore, in S2, the inert atmosphere includes nitrogen or argon.
[0021] In another aspect, the present invention provides the use of a bimetallic single-atom catalyst containing oxygen vacancies as described in the above technical scheme or a bimetallic single-atom catalyst containing oxygen vacancies prepared by the preparation method described in the above technical scheme in treating excess sludge to produce carboxylic acid carbon sources.
[0022] Furthermore, the application is carried out in a device for hydrothermal oxidation of excess sludge, the device for hydrothermal oxidation of excess sludge comprising a raw sludge transmission system, a reaction tower, a heat exchange unit and a solid-liquid separation unit connected in sequence; the reaction tower is also connected to a heat supply unit and an air delivery unit, and the heat exchange unit is connected to the heat supply unit;
[0023] The process steps of the application are as follows:
[0024] Firstly, the residual sludge is transported to the reaction tower by using the raw sludge transmission system, and then the bimetallic single atom catalyst containing oxygen vacancies is added into the reaction tower, an oxidant is introduced into the reaction tower through an air transport unit, and the reaction tower is heated by using a heat supply unit. The bimetallic single atom catalyst containing oxygen vacancies reacts with the residual sludge by hydrothermal oxidation, the residual sludge is broken down and a carboxylic acid carbon source is generated, and the solid-liquid mixture formed after the hydrothermal oxidation reaction is cooled by a heat exchange unit, and after cooling, the solid-liquid mixture enters a solid-liquid separation unit for solid-liquid separation, and the separated supernatant and filter cake resources are collected respectively.
[0025] Furthermore, the conditions of the hydrothermal oxidation reaction are: reaction pressure 1.0-5.0 MPa, reaction temperature 140-200°C, volume space velocity 0.5-2.0 h -1 , the oxidant is oxygen in the air.
[0026] The beneficial effects of the present invention are:
[0027] The present invention discloses a bimetallic single-atom catalyst containing oxygen vacancies. The bimetallic oxide is used as a carrier, which can improve the interface interaction of the catalyst carrier to promote the generation of more abundant surface oxygen vacancies. The single-atom active metal used can promote the synergistic effect with the oxygen vacancies, accelerate electron transfer, and strengthen the generation of free radicals on the catalyst surface, thereby improving the HTO catalytic activity. The improvement of the catalytic activity can improve the degradation degree of sludge extracellular polymers, so that more organic matter in the sludge enters the sludge liquid phase, making the sludge decomposition more thorough, and at the same time can also improve the product selectivity of organic C2-C4 carboxylic acids. The catalyst can realize the HTO resource treatment of sludge under conditions below 200°C without causing secondary pollution. Through the inherent acid-base catalytic properties of the bimetallic active sites and defective oxygen on the catalyst surface, the efficiency of residual sludge decomposition and hydrolysis reaction can be greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 A schematic diagram of the structure of a device for treating excess sludge using the catalyst prepared by the present invention;
[0030] Figure 2 It is a schematic diagram of the structure of a small test device used when treating excess sludge using the catalyst prepared in an embodiment of the present invention.
[0031] In the figure:
[0032] 1. Heat supply unit; 2. Reaction tower; 3. Heat exchange unit; 4. Solid-liquid separation unit; 5. Carbon source conveying pipeline; 6. Mud cake transfer vehicle; 7. Air pipeline; 8. Raw sludge transmission pipeline; 9. Cold water pipeline; 10. Heat circulation pipeline; 11. Heating furnace; 12. Reactor; 13. Heat exchanger; 14. Sample storage tank; 15. Air conveying pipeline; 16. Air pressure valve; 17. Gas flow meter; 18. Temperature measuring device; 19. Sampling pipeline; 20. Exhaust pipeline; 21. Vent pipeline; 22. Electronic scale. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Embodiment 1:
[0035] Preparation of Fe1(1.0)Ru1(1.0)@Ti(0.6) / Zr(0.4)-Ov catalyst comprises the following steps:
[0036] S1: Preparation of composite oxide support Ti(0.6) / Zr(0.4)-Ov containing oxygen vacancies by hydrothermal method
[0037] 10g TiO 2 with ZrO 2 A mixture of (TiO 2 60%, ZrO 240%) was dispersed in 200 mL of ethanol and ultrasonicated for 30 min. The mixture was transferred to a 500 mL Teflon-lined stainless steel hydrothermal reactor and heated at 200°C for 12 h. After cooling to room temperature, the solid product was centrifuged and washed three times with deionized water and alcohol, respectively, and dried in an oven at 80°C to constant weight to obtain a Ti(0.6) / Zr(0.4)-Ov carrier containing oxygen vacancies;
[0038] S2: The active metal is dispersed on the carrier in the form of single atoms by impregnation method:
[0039] 0.05g of ferric nitrate and 0.05g of ruthenium nitrate were dissolved in 50mL of an aqueous solution containing 10wt.% nitric acid to obtain a solution containing active metals, and 5g of the Ti(0.6) / Zr(0.4)-Ov carrier obtained above was impregnated in the solution, ultrasonically impregnated for 1.0h, and then dried in a 60°C vacuum oven to constant weight. The dried product was calcined for 34h in a nitrogen atmosphere at a calcination temperature of 450°C; the calcined product was rinsed three times with deionized water and 10wt.% nitric acid, respectively, and dried in a 60°C vacuum oven to obtain a Fe1(1.0)Ru1(1.0)@Ti(0.6) / Zr(0.4)-Ov bimetallic single atom catalyst containing oxygen vacancies with a Fe loading of 1.0wt.% and a Ru loading of 1.0wt.%.
[0040] Embodiment 2:
[0041] The preparation of Mn1(1.0)Pd1(1.0)@Ti(0.6) / Zr(0.4)-Ov catalyst comprises the following steps:
[0042] S1: Preparation of composite oxide support Ti(0.6) / Zr(0.4)-Ov containing oxygen vacancies by hydrothermal method
[0043] 10g TiO 2 With ZrO 2 A mixture of (TiO 2 60%, ZrO 2 40%) was dispersed in 200 mL of ethanol and ultrasonicated for 30 min. The mixture was transferred to a 500 mL Teflon-lined stainless steel hydrothermal reactor and heated at 200°C for 12 h. After cooling to room temperature, the solid product was centrifuged and washed three times with deionized water and alcohol, respectively, and dried in an oven at 80°C to constant weight to obtain a Ti(0.6) / Zr(0.4)-Ov carrier containing oxygen vacancies;
[0044] S2: The active metal is dispersed on the carrier in the form of single atoms by impregnation method:
[0045] 0.05g of manganese nitrate and 0.05g of palladium nitrate were dissolved in 50mL of an aqueous solution containing 10wt.% nitric acid to obtain a solution containing active metals. 5g of the Ti(0.6) / Zr(0.4)-Ov carrier obtained above was immersed in the solution, ultrasonically immersed for 1.0h and then dried in a 60°C vacuum oven to constant weight. The dried product was calcined for 4h under a nitrogen atmosphere at a calcination temperature of 450°C; the calcined product was rinsed three times with deionized water and 10wt.% nitric acid, respectively, and dried in a 60°C vacuum oven to obtain a Mn1(1.0)Pd1(1.0)@Ti(0.6) / Zr(0.4)-Ov bimetallic single atom catalyst containing oxygen vacancies with a Mn loading of 1.0wt.% and a Pd loading of 1.0wt.%.
[0046] Embodiment 3:
[0047] Preparation of Cu1(1.0)Ru1(1.0)@Ti(0.6) / Zr(0.4)-Ov catalyst comprises the following steps:
[0048] S1: Preparation of composite oxide support Ti(0.6) / Zr(0.4)-Ov containing oxygen vacancies Ov by hydrothermal method:
[0049] 10g TiO 2 with ZrO 2 A mixture of (TiO 2 60%, ZrO 2 40%) was dispersed in 200 mL of ethanol and ultrasonicated for 30 min. The mixture was transferred to a 500 mL Teflon-lined stainless steel hydrothermal reactor and heated at 200 °C for 12 h. After cooling to room temperature, it was centrifuged. The solid product was washed three times with deionized water and alcohol, respectively, and dried in an oven at 80 °C to constant weight to obtain a Ti(0.6) / Zr(0.4)-Ov carrier containing oxygen vacancies.
[0050] S2: The active metal is dispersed on the carrier in the form of single atoms by impregnation method:
[0051] 0.05g of copper nitrate and 0.05g of ruthenium nitrate were dissolved in 50mL of an aqueous solution containing 10wt.% nitric acid to obtain a solution containing active metals. 5g of the Ti(0.6) / Zr(0.4)-Ov carrier obtained above was immersed in the solution, ultrasonically immersed for 1.0h and then dried in a 60°C vacuum oven to constant weight. The dried product was calcined for 4h in a nitrogen atmosphere at a calcination temperature of 450°C; the calcined product was rinsed three times with deionized water and 10wt.% nitric acid, respectively, and dried in a 60°C vacuum oven to obtain a Cu1(1.0)Ru1(1.0)@Ti(0.6) / Zr(0.4)-Ov bimetallic single atom catalyst containing oxygen vacancies with a Mn loading of 1.0wt.% and a Pd loading of 1.0wt.%.
[0052] Example 4
[0053] Preparation of Fe1(2.0)Ru1(2.0)@Ti(0.6) / Zr(0.4)-Ov catalyst comprises the following steps:
[0054] S1: Preparation of composite oxide support Ti(0.6) / Zr(0.4)-Ov containing oxygen vacancies Ov by hydrothermal method:
[0055] 10g TiO 2 With ZrO 2 A mixture of (TiO 2 60%, ZrO 2 40%) was dispersed in 200 mL of ethanol and ultrasonicated for 30 min. The mixture was transferred to a 500 mL Teflon-lined stainless steel hydrothermal reactor and heated at 200°C for 12 h. After cooling to room temperature, the solid product was centrifuged and washed three times with deionized water and alcohol, respectively, and dried in an oven at 80°C to constant weight to obtain a Ti(0.6) / Zr(0.4)-Ov carrier containing oxygen vacancies;
[0056] S2: The active metal is dispersed on the carrier in the form of single atoms by impregnation method:
[0057] 0.1g of ferric nitrate and 0.1g of ruthenium nitrate were dissolved in 50mL of an aqueous solution containing 10wt.% nitric acid to obtain a solution containing active metals. 5g of the Ti(0.6) / Zr(0.4)-Ov carrier obtained above was immersed in the solution, ultrasonically immersed for 1.0h and then dried in a 60℃ vacuum oven to constant weight. The dried product was calcined for 4h under a nitrogen atmosphere at a calcination temperature of 450℃; the calcined product was rinsed three times with deionized water and 10wt.% nitric acid, respectively, and dried in a 60℃ vacuum oven to obtain a Fe1(2.0)Ru1(1.0)@Ti(0.6) / Zr(0.4)-Ov bimetallic single atom catalyst containing oxygen vacancies with a Fe loading of 1.0wt.% and a Ru loading of 1.0wt.%.
[0058] Embodiment 5:
[0059] Preparation of Fe1(1.0)Ru1(1.0)@Ti(0.6) / Al(0.4)-Ov catalyst, comprising the following steps:
[0060] S1: Preparation of composite oxide support Ti(0.6) / Al(0.4)-Ov containing oxygen vacancies Ov by hydrothermal method:
[0061] 10g TiO 2 With Al 2 O 3 A mixture of (TiO2 60%、Al 2 O 3 40%) was dispersed in 200 mL of ethanol and ultrasonicated for 30 min. The mixture was transferred to a 500 mL Teflon-lined stainless steel hydrothermal reactor and heated at 250°C for 24 h. After cooling to room temperature, the solid product was centrifuged and washed three times with deionized water and alcohol, respectively, and dried in an oven at 80°C to constant weight to obtain a Ti(0.6) / Al(0.4)-Ov carrier containing oxygen vacancies Ov.
[0062] S2: The active metal is dispersed on the carrier in the form of single atoms by impregnation method:
[0063] A nitrate containing 0.05g of the first metal Fe and 0.05g of the second metal Ru was dissolved in 50mL of an aqueous solution containing 10wt.% nitric acid to obtain a solution containing active metals, and 5g of the Ti(0.6) / Al(0.4)-Ov carrier obtained above was impregnated in the solution, ultrasonically impregnated for 1.0h, and then dried in a 60°C vacuum oven to constant weight. The dried product was calcined for 3h in a nitrogen atmosphere at a calcination temperature of 500°C; the calcined product was rinsed three times with deionized water and 10wt.% nitric acid, respectively, and dried in a 60°C vacuum oven to obtain a Fe1(1.0)Ru1(1.0)@Ti(0.6) / Al(0.4)-Ov bimetallic single atom catalyst containing oxygen vacancies with a Fe loading of 1.0wt.% and a Ru loading of 1.0wt.%.
[0064] Embodiment 6:
[0065] Preparation of Fe1(0.2)Ru1(0.2)@Ti(0.8) / Zr(0.2)-Ov catalyst comprises the following steps:
[0066] S1: Preparation of composite oxide support Ti(0.8) / Zr(0.2)-Ov containing oxygen vacancies Ov by hydrothermal method:
[0067] 10g TiO 2 With ZrO 2 A mixture of (TiO 2 80% ZrO 2 20%) was dispersed in 200 mL of ethanol and ultrasonicated for 30 min. The mixture was transferred to a 500 mL Teflon-lined stainless steel hydrothermal reactor and heated at 150°C for 12 h. After cooling to room temperature, the solid product was centrifuged and washed three times with deionized water and alcohol, respectively, and dried in an oven at 80°C to constant weight to obtain a Ti(0.8) / Zr(0.2)-Ov carrier containing oxygen vacancies;
[0068] S2: The active metal is dispersed on the carrier in the form of single atoms by impregnation method:
[0069] 0.01g of ferric nitrate and 0.01g of ruthenium nitrate were dissolved in 50mL of an aqueous solution containing 10wt.% nitric acid to obtain a solution containing active metals, and 5g of the Ti(0.8) / Zr(0.2)-Ov carrier obtained above was impregnated in the solution, ultrasonically impregnated for 1.0h, and then dried in a 60°C vacuum oven to constant weight. The dried product was calcined for 4h under a nitrogen atmosphere at a calcination temperature of 400°C; the calcined product was rinsed three times with deionized water and 10wt.% nitric acid, respectively, and dried in a 60°C vacuum oven to obtain a Fe1(0.2)Ru1(0.2)@Ti(0.8) / Zr(0.2)-Ov bimetallic single atom catalyst containing oxygen vacancies with a Fe loading of 0.2wt.% and a Ru loading of 0.2wt.%.
[0070] Embodiment 7:
[0071] Preparation of Fe1(5.0)Ru1(5.0)@Ti(0.2) / Zr(0.8)-Ov catalyst comprises the following steps:
[0072] S1: Preparation of composite oxide support Ti(0.2) / Zr(0.8)-Ov containing oxygen vacancies Ov by hydrothermal method:
[0073] 10g TiO 2 with ZrO 2 A mixture of (TiO 2 20%, ZrO 2 80%) was dispersed in 200 mL of ethanol and ultrasonicated for 30 min. The mixture was transferred to a 500 mL Teflon-lined stainless steel hydrothermal reactor and heated at 250°C for 12 h. After cooling to room temperature, the solid product was centrifuged and washed three times with deionized water and alcohol, respectively, and dried in an oven at 80°C to constant weight to obtain a Ti(0.2) / Zr(0.8)-Ov carrier containing oxygen vacancies;
[0074] S2: The active metal is dispersed on the carrier in the form of single atoms by impregnation method:
[0075] 0.25g of ferric nitrate and 0.25g of ruthenium nitrate were dissolved in 50mL of an aqueous solution containing 10wt.% nitric acid to obtain a solution containing active metals, and 5g of the Ti(0.2) / Zr(0.8)-Ov carrier obtained above was impregnated in the solution, ultrasonically impregnated for 1.0h, and then dried in a 60°C vacuum oven to constant weight. The dried product was calcined for 4h in a nitrogen atmosphere at a calcination temperature of 600°C; the calcined product was rinsed three times with deionized water and 10wt.% nitric acid, respectively, and dried in a 60°C vacuum oven to obtain a Fe1(5.0)Ru1(5.0)@Ti(0.2) / Zr(0.8)-Ov bimetallic single atom catalyst containing oxygen vacancies with a Fe loading of 5.0wt.% and a Ru loading of 5.0wt.%.
[0076] 1. Performance test:
[0077] Evaluate catalyst effects and reaction conditions through laboratory tests
[0078] 1. Laboratory test device: Figure 2 The 200 mL fixed bed reactor (model: CWAO-DA480) shown was developed by the Dalian Institute of Chemical Physics, Chinese Academy of Sciences. The process can be scaled up proportionally;
[0079] 2. The pilot test process is as follows: first, the catalyst is put into the reactor, and then the remaining sludge is transported to the fixed bed reactor through a high-pressure sludge pump, air is introduced into the reactor through an air delivery unit (a selection valve, a pressure relief valve, and a gas flow regulating valve are provided on the air delivery pipeline), and the heat source required for the reaction is provided to the reactor through a heating furnace. The catalyst and the remaining sludge undergo hydrolysis and oxidation reactions in the reactor, and the material obtained after the reaction is cooled by a heat exchanger, and the cooled solid-liquid mixture enters a sample storage tank, and finally the solid-liquid mixture in the sample storage tank is separated and filtered by a solid-liquid separation unit, and the supernatant obtained is the carboxylic acid carbon source;
[0080] 3. Catalyst evaluation method: The bimetallic single-atom catalyst containing oxygen vacancies prepared in Examples 1 to 7 was used to treat the residual sludge. At the same time, the reaction without adding catalyst was used as the control group. The catalyst evaluation test was performed in the HTO laboratory test. 200 mL of catalyst was added, and the sludge pump was used for sampling. Air was introduced as an oxidant. The reaction temperature was set to 180°C, the reaction pressure was set to 2.0 MPa, and the reaction contact time was set to 1.0 h (volume space velocity 1.0 h -1 ) After the first 8 hours of sample release, samples were taken every 6 hours. Each condition was sampled 3 times and the results were averaged.
[0081] Catalyst evaluation result analysis method: After the reaction, the sample was filtered, and the supernatant was tested for soluble COD using the national standard method and VFAs using high performance liquid chromatography; the mud cake was tested for moisture content, TS, and VS. The sample was refrigerated and stored at 4°C.
[0082] 4. Catalyst evaluation results:
[0083] The Fe1(1.0)Ru1(1.0)@Ti(0.6) / Zr(0.4)-Ov catalyst prepared in Example 1 was used to treat municipal sludge. The COD of the sludge pyrolysis liquid after HTO treatment was 15660 mg / L. Lactic acid 1123 mg / L (COD 1196.7 mg / L), acetic acid 1645 mg / L (COD 1753.0 mg / L), propionic acid 6810.3 mg / L (COD 10295.7 mg / L), butyric acid 456.3 mg / L (COD 134.3 mg / L) were detected in the pyrolysis liquid. 828.5mg / L), carboxylic acids contributed 14074mg / L COD, accounting for 89.9% of the total COD; the VS / TS of the filter cake after HTO treatment decreased from 0.69 to 0.12, indicating that the Fe1(1.0)Ru1(1.0)@Ti(0.6) / Zr(0.4)-Ov bimetallic single-atom catalyst containing oxygen vacancies prepared in Example 1 can improve the degradation degree of sludge extracellular polymers, thereby improving the efficiency of the sludge hydrolysis reaction, making the sludge breakdown more thorough and achieving deep sludge breakdown. At the same time, the improvement of the breakdown degree of sludge extracellular polymers also allows more organic matter in the sludge to be released and mainly catalytically oxidized to C2~C4 carboxylic acids.
[0085] The Mn1(1.0)Pd1(1.0)@Ti(0.6) / Zr(0.4)-Ov catalyst prepared in Example 2 was used to treat municipal sludge. The COD of the sludge pyrolysis liquid after HTO treatment was 16100 mg / L. Lactic acid 224.3 mg / L (COD 239.0 mg / L), acetic acid 1712.3 mg / L (COD 1824.8 mg / L), propionic acid 6666.7 mg / L (COD 10078.6 mg / L), and butyric acid 1120.0 mg / L (COD 2033.7 mg / L) were detected in the pyrolysis liquid. The COD contributed by carboxylic acids was 14176.1 mg / L, accounting for 88.1% of the total COD. The VS / TS of the filter cake after HTO treatment dropped from 0.69 to 0.12, indicating that the bimetallic single-atom catalyst containing oxygen vacancies in Mn1(1.0)Pd1(1.0)@Ti(0.6) / Zr(0.4)-Ov prepared in Example 2 can improve the degradation degree of sludge extracellular polymers, thereby improving the efficiency of the sludge hydrolysis reaction, making the sludge breakdown more thorough and achieving deep sludge breakdown. At the same time, the improvement in the breakdown degree of sludge extracellular polymers also allows more organic matter in the sludge to be released and mainly catalytically oxidized to C2~C4 carboxylic acids.
[0086] The Cu1(1.0)Ru1(1.0)@Ti(0.6) / Zr(0.4)-Ov catalyst prepared in Example 3 was used to treat municipal sludge. The COD of the sludge pyrolysis liquid after HTO treatment was 14785 mg / L. Lactic acid 597.2 mg / L (COD 636.4 mg / L), acetic acid 1555.0 mg / L (COD 1657.1 mg / L), propionic acid 5882.3 mg / L (COD 8892.8 mg / L), and butyric acid 1004.8 mg / L (COD 1824.5 mg / L) were detected in the pyrolysis liquid. The COD contributed by carboxylic acids was 13010.8 mg / L, accounting for 88.0% of the total COD. The VS / TS of the filter cake after HTO treatment dropped from 0.69 to 0.12, indicating that the Cu1(1.0)Ru1(1.0)@Ti(0.6) / Zr(0.4)-Ov bimetallic single-atom catalyst containing oxygen vacancies prepared in Example 3 can improve the degradation degree of sludge extracellular polymers, thereby improving the efficiency of the sludge hydrolysis reaction, making the sludge breakdown more thorough and achieving deep sludge breakdown. At the same time, the improvement in the breakdown degree of sludge extracellular polymers also allows more organic matter in the sludge to be released and mainly catalytically oxidized to C2~C4 carboxylic acids.
[0087] The Fe1(2.0)Ru1(2.0)@Ti(0.6) / Zr(0.4)-Ov catalyst prepared in Example 4 was used to treat municipal sludge. The COD of the sludge pyrolysis liquid after HTO treatment was 15000 mg / L. Lactic acid 1026.0 mg / L (COD 1093.4 mg / L), acetic acid 2114.4 mg / L (COD 2253.3 mg / L), propionic acid 5566.7 mg / L (COD 8415.7 mg / L), and butyric acid 1122.3 mg / L (COD 2037.9 mg / L) were detected in the pyrolysis liquid. The COD contributed by carboxylic acids was 13800 mg / L, accounting for 92.0% of the total COD. The VS / TS of the filter cake after HTO treatment dropped from 0.69 to 0.11, indicating that the Fe1(2.0)Ru1(1.0)@Ti(0.6) / Zr(0.4)-Ov bimetallic single-atom catalyst containing oxygen vacancies prepared in Example 4 can improve the degradation degree of sludge extracellular polymers, thereby improving the efficiency of the sludge hydrolysis reaction, making the sludge breakdown more thorough and achieving deep sludge breakdown. At the same time, the improvement in the breakdown degree of sludge extracellular polymers also allows more organic matter in the sludge to be released and mainly catalytically oxidized to C2~C4 carboxylic acids.
[0088] The Fe1(1.0)Ru1(1.0)@Ti(0.6) / Al(0.4)-Ov catalyst prepared in Example 5 was used to treat municipal sludge. The COD of the sludge pyrolysis liquid after HTO treatment was 12659 mg / L. Lactic acid 999.7 mg / L (COD 1065.3 mg / L), acetic acid 1765.7 mg / L (COD 1881.7 mg / L), propionic acid 4235.7 mg / L (COD 6403.5 mg / L), and butyric acid 1000.2 mg / L (COD 1816.2 mg / L) were detected in the pyrolysis liquid. The COD contributed by carboxylic acids was 11166.6 mg / L, accounting for 88.2% of the total COD. The VS / TS of the filter cake after HTO treatment decreased from 0.69 to 0.13, indicating that the Fe1(1.0)Ru1(1.0)@Ti(0.6) / Al(0.4)-Ov bimetallic single-atom catalyst containing oxygen vacancies prepared in Example 5 can improve the degradation degree of sludge extracellular polymers, thereby improving the efficiency of the sludge hydrolysis reaction, making the sludge breakdown more thorough and achieving deep sludge breakdown. At the same time, the improvement in the breakdown degree of sludge extracellular polymers also allows more organic matter in the sludge to be released and mainly catalytically oxidized to C2~C4 carboxylic acids.
[0089] The Fe1(0.2)Ru1(0.2)@Ti(0.8) / Zr(0.2)-Ov catalyst prepared in Example 6 was used to treat municipal sludge. The COD of the sludge pyrolysis liquid after HTO treatment was 10008 mg / L. Lactic acid 672.1 mg / L (COD 716.2 mg / L), acetic acid 996.7 mg / L (COD 1062.2 mg / L), propionic acid 3233.4 mg / L (COD 4888.2 mg / L), and butyric acid 899.9 mg / L (COD 1634.0 mg / L) were detected in the pyrolysis liquid. The COD contributed by carboxylic acids was 8300.6 mg / L, accounting for 82.9% of the total COD. The VS / TS of the filter cake after HTO treatment dropped from 0.69 to 0.20, indicating that the Fe1(0.2)Ru1(0.2)@Ti(0.8) / Zr(0.2)-Ov bimetallic single-atom catalyst containing oxygen vacancies prepared in Example 7 can improve the degradation degree of sludge extracellular polymers, thereby improving the efficiency of the sludge hydrolysis reaction, making the sludge breakdown more thorough and achieving deep sludge breakdown. At the same time, the improvement in the breakdown degree of sludge extracellular polymers also allows more organic matter in the sludge to be released and mainly catalytically oxidized to C2~C4 carboxylic acids.
[0090] The Fe1(5.0)Ru1(5.0)@Ti(0.2) / Zr(0.8)-Ov catalyst prepared in Example 7 was used to treat municipal sludge. The COD of the sludge pyrolysis liquid after HTO treatment was 10027 mg / L. Lactic acid 1224.1 mg / L (COD 1304.5 mg / L), acetic acid 2111.5 mg / L (COD 2250.2 mg / L), propionic acid 2314.8 mg / L (COD 3499.5 mg / L), and butyric acid 766.3 mg / L (COD 1391.4 mg / L) were detected in the pyrolysis liquid. The COD contributed by carboxylic acids was 11166.6 mg / L, accounting for 84.2% of the total COD. The VS / TS of the filter cake after HTO treatment dropped from 0.69 to 0.10, indicating that the Fe1(5.0)Ru1(5.0)@Ti(0.2) / Zr(0.8)-Ov bimetallic single-atom catalyst containing oxygen vacancies prepared in Example 7 can improve the degradation degree of sludge extracellular polymers, thereby improving the efficiency of the sludge hydrolysis reaction, making the sludge breakdown more thorough and achieving deep sludge breakdown. At the same time, the improvement in the breakdown degree of sludge extracellular polymers also allows more organic matter in the sludge to be released and mainly catalytically oxidized to C2~C4 carboxylic acids.
[0092] In the control group, after 97% municipal sludge was treated with HTO without the addition of a bimetallic single-atom catalyst containing oxygen vacancies, the COD of the sludge pyrolysis liquid was 8339 mg / L, and oxalic acid 20.1 mg / L, pyruvic acid 13.4 mg / L, glycolic acid 585.2 mg / L, formic acid 262.3 mg / L, acetic acid 316.9 mg / L, propionic acid 1165.9 mg / L, butyric acid 653.8 mg / L, isovaleric acid 214 mg / L were detected, and the contribution of carboxylic acid COD accounted for 50.4%. After the reaction, the sludge VS / TS dropped from 0.69 to 0.59.
[0093] Therefore, compared with the treatment of residual sludge in the control group without the addition of bimetallic single-atom catalysts containing oxygen vacancies, the catalysts prepared using Examples 1-7 can greatly improve the efficiency of sludge breakdown and hydrolysis reactions through the inherent acid-base catalytic properties of the bimetallic active sites and defective oxygen on the catalyst surface. The sludge breakdown effect is better, and organic matter can be released and mainly catalytically oxidized into C2~C4 carboxylic acids, which is convenient for resource utilization.
[0094] 5. Reaction condition evaluation method: Take the catalyst prepared in Example 1 for HTO test, and carry out HTO test in the above-mentioned 10-hour device to examine the reaction temperature (140-200°C), reaction pressure (1.0-5.0MPa), reaction contact time (volume space velocity 0.5-2.0h -1 )’s impact.
[0095] Reaction condition evaluation result analysis method: After the reaction, the sample was filtered, and the supernatant was tested for soluble COD using the national standard method and VFAs using high performance liquid chromatography; the mud cake was tested for moisture content, TS, and VS. The sample was refrigerated and stored at 4°C.
[0096] 6. Reaction condition evaluation results:
[0097] (1) Effect of reaction pressure
[0098] Reaction temperature 180℃, reaction contact time 1.0h (volume space velocity 1.0h -1 ), the reaction pressure was set to 1.0, 2.0, 3.0, 4.0, and 5.0 MPa respectively, and the results are as follows:
[0099]
[0100] From the above results, it can be seen that within the range of 1.0-5.0MPa, the sludge is well broken down, the organic matter is well released, and more than 80% of the pollutants are converted into carboxylic acid products, which is beneficial for subsequent application as a carbon source. The increase in reaction pressure is beneficial to the deep breakdown of sludge and the removal of organic pollutants, which is beneficial to reducing the VS / TS of sludge after treatment and improving the degree of stabilization. However, with the increase in pressure, the oxidation capacity is enhanced, and the degree of complete mineralization of pollutants becomes higher, resulting in a decrease in the proportion of carboxylic acid COD in the pyrolysis solution.
[0101] (2) Effect of reaction temperature
[0102] Reaction pressure 2.0MPa, volume space velocity 1.0h -1 , the reaction temperatures were set at 140, 160, 180, and 200°C, respectively. The results are as follows:
[0103]
[0104] From the above results, it can be seen that within the range of 140-200°C, the sludge is well broken down, the organic matter is well released, and more than 80% of the pollutants are converted into carboxylic acid products, which is beneficial for subsequent application as a carbon source. The increase in reaction temperature is conducive to the deep breakdown of sludge and the removal of organic pollutants, which is beneficial to reducing the VS / TS of sludge after treatment and improving the degree of stabilization. However, with the increase in temperature, the oxidation capacity is enhanced, and the degree of complete mineralization of pollutants becomes higher, resulting in a decrease in the proportion of carboxylic acid COD in the pyrolysis solution.
[0105] (3) Effect of reaction contact time
[0106] The reaction pressure was 2.0 MPa, the reaction temperature was 180°C, and the volumetric space velocity was set to 0.5 h -1 , 1.0h -1 , 2.0h-1 , that is, the reaction contact time is 2.0h, 1.0h, 0.5h, and the results are as follows:
[0107]
[0108] From the above results, it can be seen that within the range of 0.5 to 2.0 h of reaction contact time, the sludge is well broken down, the organic matter is well released, and more than 80% of the pollutants are converted into carboxylic acid products, which is beneficial for subsequent application as a carbon source. The extension of the reaction contact time is beneficial to the deep breakdown of the sludge and the removal of organic pollutants, which is beneficial to reduce the VS / TS of the sludge after treatment and improve the degree of stabilization. However, as the contact time increases, the degree of oxidation becomes deeper, and the degree of complete mineralization of the pollutants becomes higher, resulting in a decrease in the proportion of carboxylic acid COD in the pyrolysis solution. A shorter reaction contact time will lead to incomplete sludge breakdown, resulting in a higher VS / TS.
[0109] 2. Process testing:
[0110] The process of the process test of using the bimetallic single atom catalyst containing oxygen vacancies prepared by the present invention to treat excess sludge and simultaneously prepare a carboxylic acid carbon source is as follows:
[0111] like Figure 1 The figure shows the structure of the device used when the catalyst prepared by the present invention is used to treat excess sludge. The reaction tower 2 is connected to the heat exchange unit 3, the heat exchange unit is connected to the solid-liquid separation unit 4, the heat supply unit 1 (boiler) is connected to the reaction tower 2, and the heat exchange unit 3 is connected to the heat supply unit 1 (boiler); firstly, the catalyst is put into the reaction tower of the device, the excess sludge is transported to the reaction tower through the biological material transport unit, air is introduced into the reaction tower through the air transport unit, the heat source required for the reaction is provided to the reaction tower through the heat supply unit, and the catalyst and the excess sludge undergo a hydrothermal oxidation reaction. The remaining sludge is effectively broken down. The material obtained after the reaction is cooled by the heat exchange unit. The heat generated by the cooling of the reactants is recovered by the heat exchange unit and transported to the heat supply unit to achieve heat recovery and circulation. The cooled material is separated by the solid-liquid separation unit, and the supernatant obtained is the carboxylic acid carbon source, which can be used as a composite carbon source in the process of sewage treatment to achieve resource utilization. The main inorganic components of the solid mud cake obtained are oxides of silicon, aluminum, calcium, iron, etc. and trace heavy metals, which can be used as inorganic fillers for packaging cardboard, and can also be fired into ceramsite and catalysts for further resource utilization.
[0112] The Fe1(1.0)Ru1(1.0)@Ti(0.6) / Zr(0.4)-Ov catalyst prepared in Example 1 was selected. Figure 1In the process shown, the process test of HTO resource treatment of municipal sludge was carried out, the reaction temperature was 180°C, the reaction pressure was 2.0MPa, the reaction contact time was 1.0h, and the sludge from the sewage treatment plant was treated in situ (sludge moisture content 98%±1%). Since the properties of daily sludge (such as pollution degree, distribution of pollutants contained, etc.) changed according to the actual daily sewage treatment conditions, the VS / TS of the treated sludge was between 0.12 and 0.17, and the COD of the pyrolysis liquid was above 10000mg / L and below 20000mg / L, of which carboxylic acid products accounted for more than 80%, up to 99%, and the main products were C2~C4 monoacids and diacids.
[0113] In summary, the catalyst of a bimetallic single atom containing oxygen vacancies disclosed in the present invention can improve the efficiency of sludge cracking and hydrolysis reactions through the inherent acid-base catalytic properties of the bimetallic active sites and defective oxygen on the catalyst surface; the bimetallic on the catalyst surface can form more active sites, which helps to promote catalytic activity; the catalyst uses bimetallic oxides as carriers, which can improve the interfacial interaction of the catalyst carrier, thereby promoting the catalyst to produce more abundant surface oxygen vacancies; the single-atom active metal used can promote its synergistic effect with the oxygen vacancies on the carrier, thereby accelerating electron transfer and enhancing the generation of free radicals on the catalyst surface, thereby improving the catalytic efficiency; the synergistic effect of surface oxygen vacancies and bimetallic can regulate the reactants on the catalyst surface. Selective adsorption or activation regulates the interaction between the complex formed by the reactants on the catalyst surface and the adjacent sites on the catalyst surface, further regulates the oxidation intensity, and improves the product selectivity; and the active metal dispersed in a single atomic state avoids the risk of reduced metal activity caused by metal agglomeration on the catalyst surface, and is not easy to fall off under harsh hydrothermal conditions; therefore, the catalyst provided by the present invention can effectively degrade sludge extracellular polymers, can greatly improve the efficiency of sludge breakdown and hydrolysis reactions, achieve deep sludge breakdown, and also increase the release of sludge organic matter, and improve the product selectivity of organic matter C2~C4 carboxylic acids; in addition, the catalyst can realize sludge HTO resource treatment under conditions below 200°C without causing secondary pollution.
[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A bimetallic single-atom catalyst containing oxygen vacancies, characterized in that: The catalyst includes a carrier and two active metal components loaded on the carrier in the form of single atomic centers, wherein the carrier is a composite metal oxide containing oxygen vacancies, and the two active metal components include a first metal and a second metal, wherein the total loading amount of the first metal is a, 0.2wt%≤a≤5.0wt%, and the total loading amount of the second metal is b, 0.2wt%≤b≤5.0wt%.
2. A bimetallic single-atom catalyst containing oxygen vacancies according to claim 1, characterized in that: The first metal is selected from one of Fe, Mn and Cu, and the second metal is selected from one of Ru and Pd; The composite metal oxide containing oxygen vacancies is selected from any two metal oxides of TiO2, ZrO2 and Al2O3, and the content of each metal oxide in the two metal oxides is not less than 20%, and the mass ratio between the two metal oxides is 2:8 to 8:
2.
3. A method for preparing a bimetallic single-atom catalyst containing oxygen vacancies according to claim 2, characterized in that: The following steps are involved: S1: Preparation of composite oxide supports containing oxygen vacancies by hydrothermal method: Dispersing 10 g of the mixture of the composite metal oxides containing oxygen vacancies into 200 mL of ethanol to obtain a mixed solution, placing the mixed solution in a reactor for heating reaction after ultrasonic mixing, and after the reaction is completed, cooling, centrifuging, washing, and drying to prepare a composite oxide carrier containing oxygen vacancies; S2: The active metal is dispersed on the carrier in the form of single atoms by impregnation method: The nitrate containing the first metal and the nitrate containing the second metal are dissolved in an aqueous solution containing 10 wt.% nitric acid to obtain an aqueous solution containing active metal salts, and the composite oxide support containing oxygen vacancies prepared in S1 is impregnated in the aqueous solution containing active metal salts, and ultrasonically impregnated for 0.5 to 1.0 h, and then dried at 60°C to constant weight, and the dried product is calcined in an inactive atmosphere for 2 to 4 h at a calcination temperature of 400 to 600°C. The calcined product is rinsed and dried to prepare a single-atom catalyst containing oxygen vacancies.
4. The preparation method according to claim 3, characterized in that: In S2, the mass ratio of the composite oxide support containing oxygen vacancies, the first metal nitrate, and the second metal nitrate is 1-10: 0.02-0.05: 0.02-0.05; the volume ratio of the mass of the composite oxide support containing oxygen vacancies to the aqueous solution containing active metal salts is (0.2-3.6) g: (20-100) mL.
5. The preparation method according to claim 3, characterized in that: In S1, the mixed solution is placed in a reaction kettle and heated for 6 to 24 hours at a temperature of 150 to 250°C; The ultrasonic time is 30 minutes, and the ultrasonic frequency is 40 Hz; The centrifugation, washing and drying steps are as follows: centrifugation at 5000 r / min for 120 s, washing the obtained solid product with deionized water and alcohol three times respectively, and drying in an oven at 80° C. to constant weight.
6. The preparation method according to claim 3, characterized in that: In S2, the specific steps of rinsing and drying are as follows: the product obtained after calcination is rinsed three times with deionized water and 10 wt.% nitric acid respectively, and then placed in a vacuum oven at 60°C and dried to constant weight.
7. The preparation method according to claim 3, characterized in that: In S2, the inert atmosphere includes nitrogen or argon.
8. Use of the bimetallic single-atom catalyst containing oxygen vacancies as described in claims 1 to 2 or the bimetallic single-atom catalyst containing oxygen vacancies prepared by the preparation method according to any one of claims 3 to 7 in treating excess sludge to produce carboxylic acid carbon sources.
9. The use according to claim 8, characterized in that: The application is carried out in a device for hydrothermal oxidation of excess sludge, the device for hydrothermal oxidation of excess sludge comprising a raw sludge transmission system, a reaction tower (2), a heat exchange unit (3) and a solid-liquid separation unit (4) connected in sequence; the reaction tower (2) is also connected to a heat supply unit (1) and an air delivery unit, and the heat exchange unit (3) is connected to the heat supply unit (1); The process steps of the application are as follows: First, the residual sludge is transported to the reaction tower (2) by using a raw sludge transport system, and then the bimetallic single-atom catalyst containing oxygen vacancies is added to the reaction tower (2), and an oxidant is introduced into the reaction tower (2) through an air transport unit. The reaction tower (2) is heated by using a heat supply unit (1). The bimetallic single-atom catalyst containing oxygen vacancies catalyzes the residual sludge to undergo a hydrothermal oxidation reaction, and the residual sludge is broken down to generate a carboxylic acid carbon source. The solid-liquid mixture formed after the hydrothermal oxidation reaction is cooled by a heat exchange unit (3). After the cooling is completed, the solid-liquid mixture enters a solid-liquid separation unit (4) for solid-liquid separation, and the separated supernatant and filter cake resources are collected respectively.
10. The use according to claim 9, characterized in that: The conditions of the hydrothermal oxidation reaction are: reaction pressure 1.0-5.0 MPa, reaction temperature 140-200°C, volume space velocity 0.5-2.0 h -1 , the oxidant is oxygen in the air.